AN ANDROID-BASED POS APPS FOR HAWKER STALL - Leong, Hao Xian (Universiti Malaysia Sarawak (UNIMAS), 2020)
There are a lot of hawkers are still taking orders and remembering orders with memory or pen and papers. The traditional methods will have difficulty in handling increase of customers’ demands. Besides, pen-and-papers method is causing a lot of waste and not environmentally friendly as it uses a lot of papers. The project is about designing and building an Android-based mobile Point of Sales (POS) application for hawkers. The application is designed for hawkers to ease them in their daily business and increase efficiency to their sales process. It allows hawker to keep track on the orders and get the total amount of payment in an order. The proposed application also allows hawkers to input some remarks for them to remember more information about the customers or orders